Strategic management - Mohd. Khairuddin Hashim (Thompson, 2005)
This book is based on the idea that strategic management as a field of study and good business practice can be taught and learned systematically. The book initiates an attempt to provide a comprehensive view of strategic management as a process that has evolved over the years. In doing so, this book examines its origin, context, approaches, theories, and process, which are rarely being addressed together in other texts on strategic management. It will be useful for students, researchers, managers, policymakers and scholars who are keen to not only know, but also to learn more about strategic management.